Effect of staining and repeated firing on the surface and optical properties of lithium disilicate - Miranda, Jean S. [UNESP]; Barcellos, Aline S. P. [UNESP]; MartinelliLobo, Carolina M. [UNESP]; Caneppele, Taciana M. F. [UNESP]; Amaral, Marina; Kimpara, Estevão T. [UNESP] (Wiley, 2020)
Objective: Evaluate the effect of staining and repeated firings on color, translucency and surface proprieties of CAD/CAM lithium disilicate (LD). Material and Methods: One hundred eighty LD discs were made (ISO 6872) and distributed in different groups (n = 20): control (CO)—no treatment; single-step characterization (SC)—crystallization and staining fired together; and double step characterization (DC)—crystallization and then staining. The samples were submitted to two, four, or six firings, resulting in nine groups: COII, COIV, COVI, SCII, SCIV, SCVI, DCII, DCIV, and DCVI. The color and translucency were measured by a reflectance spectrophotometer. Surface roughness (Ra) and Vickers nano-hardness were also measured. ANOVA and Tukey statistical tests were used (α =.05). Results: Only CO and DC demonstrated significant color alterations (ΔE00 > 1.8). SC and DC did not show changes in translucency by the number of firings (P >.05); however, for CO (P =.02) these values increased. Nano-hardness was similar in all groups (P >.05). Ra values indicated differences due to the type of characterization (SC presented the highest values) and number of firings (CO and DC groups) (P <.01). Conclusion: SC promoted color, translucency, and roughness stability after repeated firings. Clinical Significance: The single characterization technic in CAD/CAM lithium disilicate presents good color, translucency, and hardness stability, which promote predictable results to monolithic restoration.
Keywords: color; lithium disilicate; repeated firing; roughness; translucency